Events and people of the beginnings of legal environmental protection in Poland - Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2005)
The actions presented in the article does not exploit all the care about the nature which the most brilliant scientists and politicians were involved in. Since early years of XXth century, exept the national organisations of environmental protection and science initiatives, there has lasted legislative activity which has aimed to protect the nature. This is completely separe issue which demands separe study. All the undertakings and plans might be a sign of a Polish sense of responsibility for environment. Modern world needs people not only rich in knowledge but above all, sensitive for needs of other people and nature that surrounds us. If the history is the best life’s teacher, then maybe it is worth to use this experienced and instructive legacy of polish scientists and initiatives, which were taken for rescuing and creating the natural environment. This history lesson might teach us the correct organizing, management and environmental protection.